Using the Hybrid Community Care Model to Examine Implementation Domains in Rural Behavioral Health: Exploratory Pilot Study - David A Wilkerson; John M Keesler; Kristin Funk (JMIR Formative Research, 2026)
Abstract Background Rural communities continue to experience behavioral health disparities associated with workforce shortages, digital exclusion, and fragmented coordination between trusted community-based supports and formal behavioral health systems. Although telehealth has expanded opportunities for care, less is known about how key implementation factors interact within hybrid behavioral health systems—coordinated systems that integrate trusted community-based support with formal digital behavioral health services—or how these interactions influence implementation and engagement across community and formal care settings. Objective This exploratory pilot study examined implementation domains relevant to hybrid behavioral health systems in rural communities using the hybrid community care model (HCCM) as the conceptual framework for survey development and interpretation of the findings. Methods A cross-sectional survey was administered to professionals and community stakeholders attending a rural community workshop in the Midwestern United States, with a 46.3% (38/82) response rate. Survey items operationalized 4 theoretically informed implementation domains: relational trust, digital system capacity, coordination, and perceived feasibility of hybrid care models. Descriptive statistics and Spearman rank-order analyses were conducted to examine preliminary associations among individual survey items. Results Spearman rank-order correlations indicated that coordination-related items demonstrated the strongest and most consistent associations, particularly among referral knowledge, collaboration between the community and behavioral health providers (BHPs), and continuity of care (ρ=0.383-0.633; P ≤.02). Perceived hybrid care feasibility demonstrated more variable associations, with respondents perceiving more limited BHP and appointment availability reporting stronger support for community-BHP partnerships (ρ=−0.471 and −0.648, respectively; P =.004 and P